Les effets des contextes territoriaux pour les intervenant·es de l’Aide sociale à l’enfance - Juliette Halifax; Eugénie Terrier (Sociétés et Jeunesses en Difficulté)
This article is based on the results of a research carried out in 2019-2020 in a county of western France about the spatial dimension of child protection system. It focuses on the specificities of social and family situations and professional practices according to local contexts. The research was based on a mixed methodology combining a qualitative survey towards child welfare social workers and a spatial analysis of available statistical data.Even if most of the risk factors known in child welfare are present in all the territories investigated, the probability of encountering them may differ from one area to another in relation to socio-demographic characteristics and the effects of territorial contexts. The research also shows the existence of strong spatial inequalities in terms of child protection services between territories. Finally, the analysis shows a spatial difference in social visibility of families difficulties as well as the weight of the spatial factor in the social construction of danger level.